Effect of anti-interleukin 12 treatment on murine lyme borreliosis. - Anguita, J (1996)
The effect of anti-interleukin (IL-12 treatment on Lyme borreliosis in C3H/HeN (C3H) mice was assessed because other studies have implicated CD4+ T cell helper (Th) type 1 responses in the genesis of disease caused by Borrelia burgdorferi. Infection of inbred mice with B. burgdorferi results in varying degrees of arthritis: BALB/c mice develop mild disease and C3H mice develop severe arthritis that is most pronounced 2-4 wk after infection. Since IL-12 is a major inducer of Th1 responses, we blocked this cytokine in vivo in B. burgdorferi infected C3H mice, and evaluated the effects of treatment on the development of arthritis at the peak of acute joint inflammation (14 d) and in the resolution phase (60 d) of disease. As expected, intraperitoneal administration of an anti-IL-12 monoclonal antibody (mAb) to C3H mice resulted in a decrease in both IFN-gamma and B. burgdorferi-specific IgG2a in serum, indicative of diminished Th1 responses. No IL-4 production was detected in serum of anti-IL-12 mAb treated or control mice. IgG1 and IgG2b levels did not increase in B. burgdorferi infected mice treated with anti-IL-12 mAb compared with controls suggesting that Th2 responses were not affected. Nevertheless, CD4+ T cells from both control and anti-IL-12 mAb treated mice had similar in vitro responses to B. burgdorferi antigens. Treatment with anti-IL-12 mAb produced a significant reduction in peak arthritis severity, and an increase in the number of spirochetes in ear tissue. These data show that treatment of B. burgdorferi infected mice with anti-IL-12 mAb results in a reduction of the Th1 and/or innate immune responses in vivo and a reduction in the severity of acute murine Lyme arthritis.